Density-independent algorithm for sensing moisture content of sawdust based on reflection measurements. (June 2017) - Julrat, Sakol; Trabelsi, Samir
Abstract : A density-independent algorithm for moisture content determination in sawdust, based on a one-port reflection measurement technique is proposed for the first time. Performance of this algorithm is demonstrated through measurement of the dielectric properties of sawdust with an open-ended half-mode substrate integrated waveguide (HMSIW) sensor. For accurate measurement of the dielectric properties of sawdust, the HMSIW sensor was calibrated by using a three-material calibration technique, with air, water and 25% ethanol aqueous solution. For moisture determination, a density-independent calibration function expressed in terms of the dielectric properties was used. Both moist and dry bulk densities were considered for the complex-plane representation of the dielectric properties. Results of moisture prediction, relative to each complex-plane representation were found to be similar at 5 GHz and 23 °C with the standard errors of performance of 0.955% and 0.957%, respectively. Highlights: A density-independent algorithm for moisture determination in sawdust is proposed. The moisture algorithm is based on dielectric properties measurement. The technique is based on a one-port reflection measurement at 5 GHz and 23 °C. Both moist and dry bulk densities were considered in the moisture algorithms. Predicted moisture compared well with standard oven method.